2018
DOI: 10.1016/j.fertnstert.2018.07.1009
|View full text |Cite
|
Sign up to set email alerts
|

Stress relief: can continuous culture in a low lactate culture media reduce numerical chromosomal abnormalities and therefore improve euploidy rates?

Abstract: Research Study. MATERIALS AND METHODS: Human zygotes with 3 pronuclei (PN) were cryopreserved with consent, thawed, and placed into control (CON; n¼23) or reduced nutrient (RN; n¼25) sequential culture medium, both supplemented with HSA. Embryos were cultured individually in an Embryo-Scope and were assessed for blastocyst development on D5 and D6. On D6, blastocysts were placed into fibronectin coated dishes for outgrowth culture in IVC1 (Cell Guidance Systems) medium, along with thawed D6 human blastocyst co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In fact, when VerMilyea et al 23 compared CSCM‐NX against other companies’ sequential mediums, cultured them to blastocysts, biopsied the trophectoderm, and performed PGT‐A to compare embryo ploidy, the euploid rate of embryos cultured in CSCM‐NX was significantly higher. VerMilyea et al reported the use of CSCM‐NX in pre‐ICSI pre‐culture, and again, it is possible that oocyte energy metabolism is improved.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, when VerMilyea et al 23 compared CSCM‐NX against other companies’ sequential mediums, cultured them to blastocysts, biopsied the trophectoderm, and performed PGT‐A to compare embryo ploidy, the euploid rate of embryos cultured in CSCM‐NX was significantly higher. VerMilyea et al reported the use of CSCM‐NX in pre‐ICSI pre‐culture, and again, it is possible that oocyte energy metabolism is improved.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study examined outcomes from two laboratories over a 2-year period, comparing a sequential media system to a low lactate continuous single step in one laboratory and comparing the same low lactate continuous single-step medium to a different continuous single-step medium in a second laboratory (Vermilya et al, 2018). Incubators for all comparisons were kept at 6% CO 2 .…”
Section: Culture Mediamentioning
confidence: 99%
“…No well-designed, prospective randomized controlled trials have compared outcomes between modern single-step medium, designed to culture embryos to the blastocyst stage, with sequential culture media. Evidence on whether singlestep media may affect fidelity of mitotic chromosome dynamics, compared with sequential media in preimplantation embryos, is conflicting (Werner et al, 2016;Fragouli et al, 2017;Vermilya et al, 2018). On the basis of emerging data about the possible effect of culture media on offspring weight and cardiovascular health (Kleijkers et al, 2014;Zandstra et al, 2015;2018), it is prudent that this remains an active area of research.…”
Section: Single-step Mediamentioning
confidence: 99%